2009
DOI: 10.1194/jlr.m800426-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl esters as a depot for very long chain fatty acids in human meibum

Abstract: Human meibomian gland secretions (also known as meibum) were analyzed for the presence of cholesteryl esters (Chl-E) using HPLC in combination with atmospheric pressure chemical ionization mass spectrometry. A special procedure based on detection of the in-source generated ion m/z 369 was developed to monitor all Chl-E simultaneously. The structures of the detected compounds were studied using in-source and postsource fragmentation of the precursor (M1H) 1 ions. In concordance with previous studies, Chl-E were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 28 publications
(55 reference statements)
7
152
1
Order By: Relevance
“…Samples were then centrifuged at 3,000 rpm at 4°C for 5 min and the lower organic phase was extracted. The aqueous resonance spectroscopy, the lipid composition of the human meibomian gland secretions, the predominant source of lipids for the precorneal tear fi lm, has been elucidated with great compositional and structural details (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). A comprehensive lipidomic analysis of the tear fl uid per se, however, has lingered behind.…”
Section: Lipid Extractionmentioning
confidence: 99%
“…Samples were then centrifuged at 3,000 rpm at 4°C for 5 min and the lower organic phase was extracted. The aqueous resonance spectroscopy, the lipid composition of the human meibomian gland secretions, the predominant source of lipids for the precorneal tear fi lm, has been elucidated with great compositional and structural details (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). A comprehensive lipidomic analysis of the tear fl uid per se, however, has lingered behind.…”
Section: Lipid Extractionmentioning
confidence: 99%
“…For both saturated CEs, the ESI technique proved to have a better signal intensity than APCI mode ( ‫ف‬ 7-to 13-fold better). Having said that, other researchers, including Butovich et al ( 26,27 ), have shown the application of APCI to measure in one analytical run free cholesterol and cholesterol esters coupled to a reversed phase column. But in their research, they were not measuring metabolic fl ux of free cholesterol and cholesterol esters in plasma.…”
Section: Gc/ms Of Total Plasma Palmitate and Cholesterolmentioning
confidence: 99%
“…The samples of normal human meibum were collected from both lower and upper eyelids of seven volunteers (three males and four females) using a platinum spatula, dried, and stored exactly as described earlier (9)(10)(11)15 ). The samples were used for structural analyses of meibomian lipids only; no conclusions about the effects of gender, age, type of diet, etc .…”
Section: Sample Collectionmentioning
confidence: 99%